Queer Be Fantasy Creatures: A Queer Reading of TJ Klune's Fantasy Novel The House in the Cerulean Sea - Helin, Nelli (My University, 2025)
This thesis offers a queer reading of TJ Klune’s The House in the Cerulean Sea (2020). Since the novel is a work of fantasy literature that includes openly queer characters, queer theory is combined with research into fantasy literature to find out how issues of prejudice and discrimination against queer people can be presented in a fantasy world setting and what purpose this setting serves in the light of these issues. The chapter for theoretical background defines the novel within the fantasy genre and specifies the scope of queer theory appropriate for the analysis. The order of the analysis goes from queer themes and characters in the novel to themes of acceptance that reflect the acceptance of minority groups in the real world. The importance of representation is also discussed concerning these themes, and lastly, a short analysis of the sequel to the novel, published in 2024, is included to finalize the discussion on the established themes. I conclude that the fantasy setting of The House in the Cerulean Sea is appropriate and even desirable to allude to issues regarding queer people in the real world. The fantasy creatures of the novel serve as the “queer” elements that must face surmise and mistreatment because they deviate from the societal “norm” and, thus, they act as an allegory for queer people and other minority groups. Furthermore, as a queer author, Klune has been able to provide positive yet authentic representations of queer people for which there is a current necessity.
Keywords: queer, fantasy, queer theory, magical creatures, acceptance, representation